DETERMINATION OF EQUIVALENT LOADS FROM ROLLING STOCK FOR LINES OF INFLUENCE OF ARBITRARY SHAPE - Sukhorukov, B. D.; Sukhorukov, S. B. (Science and Transport Progress, 2008)
The algorithm for determination of equivalent load from a rolling stock (a vehicle) with the arbitrary given scheme of location of axles and axle-loads for influence lines of any form was suggested and performed on a computer.